The Poetics of Body: Representing Cultural Imaginations in Yang Jung-Ung’s "A Midsummer Night’s Dream" - Choi, Boram (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
This article explores the psychology that motivates Yang Jung-Ung and his actors in the process of translating Shakespeare’s A Midsummer Night’s Dream into a Korean style. By focusing on the ways of showing the theme of the play in modern styles fused with traditional modes of theatrical practice, the director attempts to develop his own ways of expression to communicate with the modern Korean audience. In this process, Yang reconstructs the dialogues between the characters rather than rely heavily on Shakespeare’s text and language. For this reason, his production has often been criticised for missing Shakespeare’s poetry. However, the beauty of poetry is not only in Shakespeare’s language itself, but rather it is in the mental process of how the artist and audiences understand and translate its meaning in their cultural contexts. Shakespeare’s language includes a great deal of imagery that provides the artists with concrete information for constructing the stage mise-en-scène. In Yang’s production, Shakespeare’s poetry is expressed through the visual images created by the performer’s physical bodies, which reflects the director’s interpretation of the play in his cultural context. By analysing the performers’ physical movements, this article studies how Yang perceives the theme of Shakespeare’s Dream in relation to a Korean cultural context and presents his unique vision on the play.